Elements of German culture: An analysis of German language textbooks in Indonesian universities - Mulyani, Retna Endah Sri; Santoso, Iman; Sudarmaji, Sudarmaji (citeus, 2024)
German textbooks encompass various facets of German culture. However, teachers in Indonesia often overlook the significance of German culture. The primary objective of this study is to provide a comprehensive account of the German cultural components found within German language textbooks used in Indonesian universities. To achieve this goal, a descriptive qualitative methodology was employed, where the textbooks were analyzed according to Byram's theory of eight cultural dimensions. The utilised textbooks include Netzwerk A1, Netzwerk A2, and Netzwerk B1, which align with language skill levels A1, A2, and B1 according to the Common European Framework of Reference for Languages (CEFR). Each textbook set consists of a coursebook and a workbook. The findings of the analysis revealed that the most prevalent cultural elements encompassed social interaction, stereotypes and national identity, and socialization and life cycle. The implications of these findings indicate that social interaction, as the most prominent cultural aspect, reinforces the educational objectives of German language courses, specifically in terms of fostering the development of communicative competence. Aspek budaya Jerman: Analisis buku ajar bahasa Jerman di perguruan tinggi Indonesia Buku ajar bahasa Jerman mengandung berbagai aspek budaya Jerman. Namun demikian, keberadaan budaya Jerman tersebut sering kali diabaikan oleh para pengajar di Indonesia. Tujuan penelitian ini adalah untuk memberikan gambaran yang komprehensif mengenai komponen-komponen budaya Jerman yang terdapat dalam buku-buku ajar bahasa Jerman yang digunakan di perguruan tinggi di Indonesia. Penelitian ini merupakan penelitian kualitatif deskriptif. Data penelitian ini bersumber dari buku ajar bahasa Jerman yang mencakup tiga level penguasaan bahasa berdasarkan acuan kerangka kerja pembelajaran bahasa di Eropa (CEFR), yaitu Netzwerk A1, Netzwerk A2, dan Netzwerk B1. Ketiga buku tersebut dianalisis menggunakan teori Byram tentang delapan dimensi budaya. Temuan penelitian ini menunjukkan bahwa elemen budaya yang paling banyak ditemukan adalah interaksi sosial, stereotip dan identitas nasional, serta sosialisasi dan siklus hidup. Implikasi dari temuan ini menunjukkan bahwa interaksi sosial, sebagai aspek budaya yang paling menonjol, memperkuat tujuan pendidikan mata kuliah bahasa Jerman, khususnya dalam hal mendorong pengembangan kompetensi komunikatif.